Analysis of Marketing Strategy to Attract Shopping Interest (Case Study of Online Alms Shop, Jalan Jawa, Pematangsiantar City) - Fatwa Nasya Al Hadi; Tuti Anggraini; Rahmi Syahriza (Penerbit Jurnal Indonesia, 2022)
This study aims to identify and analyze marketing strategies to attract shopping interest at the Sedekah Online Store. The research approach used in this research is descriptive qualitative and the author uses a SWOT analysis. SWOT analysis is a systematic identification of factors to formulate a marketing strategy. Then to find out the results of the SWOT analysis in the marketing strategy to attract shopping interest using the IFAS and EFAS matrices can be identified as important factors both from the internal and external environment which are the strengths, weaknesses, opportunities and threats of shopping interest. The results of the analysis obtained is a growth oriented strategy, this strategy indicates a strong company condition and is able to continue to grow by taking the opportunities and opportunities that exist to achieve maximum turnover. This strategy was chosen because the calculation results are in quadrant I where the total score of strengths and weaknesses is 2.84 and the total score of opportunities and threats is 2.34. Positions in this quadrant are very profitable and can be applied to the fullest. Consumers' shopping interest can be increased by increasing promotions with the concept of shopping while giving charity and providing understanding to consumers about the benefits and importance of giving alms to society by using existing technological developments to make it easier for consumers to shop at the Online Alms Shop.